Analytical modeling of the bond behavior between textile and mortar based on pull-out tests - Dalalbashi, Ali (2019)
It is clear that the fiber-to-mortar bond behavior plays a major role on the performance of Textile Reinforced Mortars (TRMs) used for strengthening of existing structures. This aspect, however, has been only the subject of few studies and require further attention. This paper presents an analytical model for extraction of the textile-to-mortar bond-slip laws from pull-out tests. The objective is to characterize the parameters that influence the pull-out behavior of TRM systems. In the formulation of the pull-out model, a modified approach based on a mathematical model by Naaman is applied. Firstly, based on the experimental results, a relationship between the bond shear stress and the relative slip along the fiber-mortar interface is obtained. Then, based on the shear stress-slip law, the boundary conditions, equations of equilibrium, and the equation of compatibility and hooke’s law, the bond response between textile and mortar is predicted and modeled.